Analysis of Teachers’ Competences for Industry 4.0 Subjects: A Case of Thai Higher Education Institutions - Lima, Rui M.; Sousa, Rui M.; Costa, Lino; Jesus, Cristiano; Mesquita, Diana; Kengpol, Athakorn; Meethom, Warapoj; Koomsap, Pisut (Applied Science and Engineering Progress, 2023)
The era of Industry 4.0 (I4.0) requires technology and engineering higher education institutions to provide their students with the competences inherent to this evolution. This requires teaching staff training, but first, naturally, teachers’ level of competences must be assessed. The objective of this work is to assess the current level of teaching staff self-perceived competences related to product, process, and production in the I4.0 Era, using a tailor-made questionnaire. Additionally, the work aims to evaluate the relation between academic degrees and years of experience, with the level of self-perceived competences. In terms of methodology, the development of the questionnaire’s items was based on the Acatech framework and existing I4.0 courses. The questionnaire was validated through the following steps: 1) think-aloud procedures with 4 teaching staff, and 2) test and retest statistics validation, developed with approximately 30 teaching staff from the referred institutions. Then, the questionnaire was applied to more than 200 teaching staff. Two I4.0 areas showed a lower level of self-perceived competence: Data Analytics and Digital Manufacturing. It became evident that the teaching staff, regardless of their level of experience or academic degree, may benefit from organizational and people management training including processes and techniques related to I4.0.